Speed Control Scheme Analysis of Switched Reluctance Actuator - Pestana, Luís (2019)
This paper presents the implementation of a nonlinear model of a Linear Switched Reluctance Actuator (LRSA) in Simulink/ SimPowerSystems environment. The model is based in an already implemented motor model for the rotating machine, which was improved and adopted to be applied in the analysis of a linear actuator. Both the magnetic information from experimental data and results obtained from Finite Element Analysis (FEA) were used to perform that analysis. The model is used in the assessment of several control schemes.